2022
DOI: 10.1039/d2sc03273b
|View full text |Cite
|
Sign up to set email alerts
|

Crystal engineering of ferrocene-based charge-transfer complexes for NIR-II photothermal therapy and ferroptosis

Abstract: Organic charge-transfer complexes (CTCs) can function as versatile second near-infrared (NIR-II) theranostic platforms to tackle complicated solid tumors, while the structure-property relationship is still an unanswered problem. To uncover the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…In vivo experiments showed that the multifunctional F4TCNQ-based CTCs can effectively kill tumors under the combination of 1060 nm laser-triggered PTT and cell ferrotherapy. [16,56,101] Photothermal immunotherapy can effectively avoid the weakness of a single PTT and process a good inhibitory effect on distant tumors via immunotherapy, which has become a promising therapeutic strategy. F4TCNQ-based CTCs can combine with programmed cell death protein to suppress tumor immune evasion and improve NIR-II PTT.…”
Section: Anticancermentioning
confidence: 99%
See 1 more Smart Citation
“…In vivo experiments showed that the multifunctional F4TCNQ-based CTCs can effectively kill tumors under the combination of 1060 nm laser-triggered PTT and cell ferrotherapy. [16,56,101] Photothermal immunotherapy can effectively avoid the weakness of a single PTT and process a good inhibitory effect on distant tumors via immunotherapy, which has become a promising therapeutic strategy. F4TCNQ-based CTCs can combine with programmed cell death protein to suppress tumor immune evasion and improve NIR-II PTT.…”
Section: Anticancermentioning
confidence: 99%
“…In vivo experiments showed that the multifunctional F4TCNQ‐based CTCs can effectively kill tumors under the combination of 1060 nm laser‐triggered PTT and cell ferrotherapy. [ 16,56,101 ]…”
Section: Applications Of the Organic Photothermal Ctcsmentioning
confidence: 99%
“…The efficient intermolecular charge transfer lowers the energy gap of CTCs and thus easily expands their absorptions beyond the second NIR region (NIR-II, > 1000 nm) for PTT. [59][60][61][62] Up to now, many OOMs have been directly used or modified for highperformance bioimaging and phototherapy which exhibit great potential for disease diagnosis and therapy. [63][64][65][66][67][68][69][70] Some excellent materials can even be used for imaging diagnosis and phototherapy simultaneously which is termed "phototheranostics".…”
Section: Introductionmentioning
confidence: 99%